Enhanced primary care provided by a nurse practitioner candidate to aged care facility residents: A mixed methods study. Issue 3 (June 2020) - Craswell, Alison; Wallis, Marianne; Coates, Kaye; Marsden, Elizabeth; Taylor, Andrea; Broadbent, Marc; Nguyen, Kim-Huong; Johnston-Devin, Colleen; Glenwright, Amanda; Crilly, Julia
Abstract: Background: Residents of aged care facilities are at risk of potentially preventable hospitalisation. This risk is increased for those who are older, have more co-morbidities, are malnourished, taking multiple medications and have a history of previous falls. Aim: To evaluate the impact of a nurse practitioner candidate delivering care to acutely ill older adults living in aged care facilities. Methods: Nested in a larger program of research, this mixed methods study comprised: i) a descriptive analysis of interventions performed by the nurse practitioner candidate (prospectively collected data); and ii) a quasi-experimental study of patient and health service outcomes, including costs, for residents transferred to the local hospital emergency department from the study facility compared with residents from other aged care facilities presenting to the local hospital, in a 12-month period (retrospectively collected data). The intervention comprised a nurse practitioner candidate providing early intervention to residents with acute illness. This included: advanced assessment, enhanced primary care with the general practitioner, advanced care planning, and opportunistic education to facility staff. The study setting was one aged care provider of approximately 300 beds in regional Queensland, Australia. Findings: The nurse practitioner candidate completed 1790 consultations with 266 residents over the 12-month study period. Residents transferred to hospital had shorter median length of stay in the emergency department (Study facility: 240 mins; Other facilities: 277 min; MWU = 153972.0; p = 0.005), cost less and fewer residents required hospital admission (Study facility: 44.6%; Other facilities: 59.0%; p = 0.0001) but representations for same or any cause were higher compared to those from other facilities. There was a 300% increase in the number of residents with Advance Care Planning in the study facility. Conclusion: Introduction of a nurse practitioner candidate working with general practitioners improved most outcomes for aged care facility residents transferred to hospital and increased documentation of advance care planning.